A Literary Nahda Interrupted: Pre-Nakba Palestinian Literature as Adab Maqalat. Issue 3 (3rd July 2022) - Abdou, Ibrahim Mahfouz; Abu-Remaileh, Refqa
Abstract: This article delves into the pre-Nakba literary scene of the 1930s and 1940s by way of its literary periodicals. Following the work of Hanna Abu Hanna and Ishaq Musa al-Husseini, the article posits periodicals as a primary, albeit understudied, site of Palestinian literary production. Prior to the Nakba, the Palestinian literary landscape experienced a small-scale local nahda in the form of adab maqalat (periodical literature) rather than adab mu'allafat (monograph/book-form literature). However, due to the ruptures of 1948, this formative period of adab maqalat has been unexplored and remains disconnected from Palestinian literary histories. In the context of a larger project that reconnects fragmented "black hole" periods of Palestinian literary history, this article takes a step toward sketching the major elements of Palestine's literary landscape before the Nakba.